The Middle East and North Africa in a Changing Oil Market - Okogu, Bright (Washington, D.C. : International Monetary Fund, 2003)
The world oil market has undergone a series of changes that have reduced the share of oil in the global energy balance and, with it, the influence of Middle Eastern oil exporters. In spite of oil's loss of ground, however, Middle Eastern countries remain at the center of world oil developments. This paper focuses on the developments in the international oil market, the role of Middle Eastern countries therein, and the policy challenges arising from the dependency on oil.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet